Kajian Penambahan Konsentrasi Susu Skim Terhadap Mutu Minuman Yogurt dari Limbah Air Cucian Beras Lokal - Arjuman Leko; Vita N Lawalata; Sandriana J Nendissa (AGRITEKNO: Jurnal Teknologi Pertanian, 2018)
Water from the washing of rice during rice cooking process is considered wastewater. This rice cleansing water contains nutrients such as carbohydrates, proteins and B1 vitamin which alternatively can be used to make yogurt drink with the addition of skim milk. The purpose of this research was to obtain the exact skim milk concentration to produce the best quality of yogurt drink from rice cleansing water. A completely randomized experimental design with three levels of skim milk concentrations i.e.: 5, 10, and 15% with three replications were applied in this research. Observed variables include total acid, protein, fat, and total bacteria content, as well as an organoleptic test (viscosity, consistency, flavor, and taste). The 10% skim milk concentration was found to be the best treatment resulting in yogurt drink with total acid, protein, fat, total bacteria content of 1.11%, 3.54%, 1.55%, and 1.50 CFU/mL respectively, viscosity and taste of the organoleptic of the drink were 3.15 and 3.25 subsequently. Keywords: rice cleansing water, skim milk, yogurt drink